Azithromycin based triple therapy versus standard clarithromycin based triple therapy in eradication of Helicobacter pylori infection in Iran: a randomized controlled clinical trial - Seyed Saeid SARKESHIKIAN; Abolfazl IRANIKHAH; Mohammad Reza GHADIR (Turkish Journal of Gastroenterology, 2019)
-